Discourse Theory and Practice - Taylor Stephanie; Wetherell Margaret; Yates Simeon J (Sage Publications, 2001)
This book introduces the major figures in discourse research and charts the main themes and developments in this exciting emerging field of study. Acknowledgements, Foundations and Building Blocks, Themes in Discourse Research: The Case of Diana, From Saussure to Critical Sociolinguistics: The Turn Towards a Social View of Language, The Ethnography of Speaking, Language and Struggle and Voice, Foucault: Power and Knowledge and Discourse, Social Interaction, Footing, Rules of Conversational Sequence, The Construction of ''Delicate'' Objects in Counselling, Interethnic Communication, The Relativity of Linguistic Strategies: Rethinking Power and Solidarity in Gender and Dominance, Minds and Selves and Sense Making, Unfolding Discourse Analysis, The Multivoicedness of Meaning, Emotion, Self Narration in Social Life, Positioning: The Discursive Production of Selves, Gender Difference and the Production of Subhjectivity, Culture and Social Relations, Social Semiotics, Principles of Critical Discourse Analysis, Textualizin Global Politics, The Spectacle of the Other, Conclusion, Index.